Odpowiedzi

Najlepsza Odpowiedź!
2009-12-06T20:55:03+01:00
Witaj:)

(1¾)⁶ * (²/₇)⁶ =( 7/4 *2/7)⁶ = 1/64
(0,8)⁴ : (2⅔)⁴ = (8/10 * 3/8)⁴=3/10⁴= 81/10000
(-6,5) / (-0,13) = -65/10 * -100/13 = 50
(4½)³ * (-⅔)³ * (-2)³ = (9/2 * -2/3 * -2)³ = 6³=216
(2½) * 0,6⁴ * (-¹/₁₅)⁴= ( 5/2 * 6/10 * -1/15 )⁴= 1/10⁴=1/10000
0,3⁴ * (2⅔)⁴ / (-4)⁴ = (3/10*8/3)⁴/-4⁴= 4/5 / -4 )⁴=-1/5⁴=1/625
2009-12-06T21:04:30+01:00
Myślę że tak bd:
(1¾)⁶ * (²/₇)⁶ =1841,56
(0,8)⁴ : (2⅔)⁴=0,0081
(-6,5) / (-0,13)=50
(4½)³ * (-⅔)³ * (-2)³=216
(2½) * 0,6⁴ * (-¹/₁₅)⁴= 0,00000064
0,3⁴ * (2⅔)⁴ / (-4)⁴ =0,00016